Zwischen Romantik-Kritik und «Horen»-Kontinuität. Hölderlins «Iduna»-Projekt im Spektrum zeitgenössischer Zeitschriften (Studia theodisca, 2025)
In the summer of 1799 Friedrich Hölderlin worked intensively on the «Iduna»-project, a «humanistic journal» which was intended to earn him prestige and a steady income. As the difficulties increased and important authors declined his invitation to contribute, the enterprise was abandoned. Based on Hölderlin’s letters and drafts, this essay focuses on the program of «Iduna» with the aim of  embedding it within the context of contemporary journals at a time of great changes in society, the editorial world, and reading interests. A comparison with the most significant literary journals of the time («Die Horen», «Propyläen», «Athenaeum») not only shows striking similarities with «Die Horen», but also helps to explain why this project was doomed to failure.